Changes in the rates of weight and waist circumference gain in Australian adults over time: a longitudinal cohort study. Issue 1 (16th January 2014) - Peeters, Anna; Magliano, Dianna J; Backholer, Kathryn; Zimmet, Paul; Shaw, Jonathan E
Abstract : Objective: To assess in a single cohort whether annual weight and waist circumference (WC) change has varied over time. Design: Longitudinal cohort study with three surveys (1) 1999/2000; (2) 2004/2005 and (3) 2011/2012. Generalised linear mixed models with random effects were used to compare annualised weight and WC change between surveys 1 and 2 (period 1) with that between surveys 2 and 3 (period 2). Models were adjusted for age to analyse changes with time rather than age. Models were additionally adjusted for sex, education status, area-level socioeconomic disadvantage, ethnicity, body mass index, diabetes status and smoking status. Setting: The Australian Diabetes, Obesity and Lifestyle study (AusDiab)—a population-based, stratified-cluster survey of 11247 adults aged ≥25 years. Participants: 3351 Australian adults who attended each of three surveys and had complete measures of weight, WC and covariates. Primary outcome measures: Weight and WC were measured at each survey. Change in weight and WC was annualised for comparison between the two periods. Results: Mean weight and WC increased in both periods (0.34 kg/year, 0.43 cm/year period 1; 0.13 kg/year, 0.46 cm/year period 2). Annualised weight gain in period 2 was 0.11 kg/year (95% CI 0.06 to 0.15) less than period 1. Lesser annual weight gain between the two periods was not seen for those with greatest area-level socioeconomic disadvantage, or in men over the age of 55. In contrast, the annualised WC increase in period 2 was greater than period 1 (0.07 cm/year, 95% CI 0.01 to 0.12). The increase was greatest in men aged 55+ years and those with a greater area-level socioeconomic disadvantage. Conclusions: Between 2004/2005 and 2011/2012, Australian adults in a national study continued to gain weight, but more slowly than 1999/2000–2004/2005. While weight gain may be slowing, this was not observed for older men or those in more disadvantaged groups, and the same cannot be said for WC.